Integrating Science and Entrepreneurial Character Among Islamic Boarding School Students Through an Integrated Agribusiness Model - Afiful Ihwan; Wahidmurni; Jamiluddin Yacub (Postgraduate, University of Mataram, 2026)
This study analyzes the integration of scientific knowledge and entrepreneurial character development among santri (Islamic boarding school students) through an integrated agribusiness model at two pesantren in East Ogan Komering Ulu, Indonesia. Using a qualitative case study approach with interviews, observation, and document analysis, findings reveal that both institutions systematically combine scientific agricultural practices—such as hydroponics, organic cultivation, and sustainable resource management—with Islamic ethical principles like amanah (trustworthiness) and muamalah fiqh. Three core strategies emerged: value-infused mentorship, reflective practice, and community-engaged learning, which collectively cultivate a distinctive